Temporal changes in digestive enzyme activities in the gastrointestinal tract of European eel (Anguilla anguilla) ( Linneo 1758 ) following feeding. - CARUSO G; GENOVESE L.; DENARO, Maria Gabr. (2008)
Changes occurring after feeding in the digestive enzyme activities of European eel were investigated to provide some insights into the digestive physiology of this fish. Total and specific proteases, amylase and lipase activities were measured using standard biochemical assays over a 24 h cycle in fed eels, compared to starved ones, under the same rearing conditions. In the gastrointestinal tract of fed eels quantitative changes started 4 h after feeding and continued later on; conversely, in starved eels enzyme activities remained unchanged over time. In fed eels, total and specific protease activities showed an overall increasing trend in the intestine, while in the stomach they progressively decreased to values 22–50% lower than those measured at the pre-feeding time; this behaviour probably reflected the progression of digesta along the intestinal tract. The prolonged secretory response of European eel to food ingestion proved its extended activity in the digestive process.